VOLATILE PROFILES AND BIOLOGICAL PROPERTIES OF CYMBOPOGON CITRATUS, CYMBOPOGON GIGANTEUS, CYMBOPOGON SHOENANTHUS, AND THEIR ISOLATED COMPOUNDS: A REVIEW - BOSSOU, Annick Flore Arlette Dohoué; BOGNINOU, Gbêdossou Sophie Reine; AGBANGNAN DOSSA, Cokou P.; YEDOMONHAN, Hounnankpon; AVLESSI, Félicien; C. K. SOHOUNHLOUÉ, Dominique (Journal of Biomedical and Pharmaceutical Research, 2020)
Essential oils are worldwide used for their several biological properties. As such, the genus Cymbopogon is an interesting source of essential oils. Among the genus Cymbopogon, the most studied plant species, especially in West Africa, are C. citratus, C. giganteus and C. Schoenanthus. The essential oils extracted from these plants are sought for their various properties such as their insecticidal, analgesic, anti-inflammatory, antioxidant, hypotensive properties. Their anti-leishmaniasis, antimicrobial, antiplasmodial anti-acetylcholinesterase, anti-trypanosomal, anti-nociceptive and anticonvulsant potentials were also noted. These different properties are related to the presence of secondary metabolites in these essential oils. It follows that, the Cymbopogon species as well as the volatile compounds contained in their essential oils constitute interesting sources of new bioactive substances likely to fight against several types of resistance phenomena. Thus this literature review constitutes a scientific basis which can contribute to the economic valorization of the genus Cymbopogon.Keywors : Cymbopogon species, volatile profiles, biological properties,  cytotoxicity